Analisis Peran Pajak Bumi dan Bangunan (PBB) pada Pertumbuhan Ekonomi di Kabupaten Pasaman Barat - Fatimah Fatimah; Tartila Devy (Universitas 45 Surabaya, 2023)
This study aims to determine the role of PBB on economic growth in Kab. West Passage. The type of research used in this research is qualitative. The data processed in this study is PBB revenue for 2016-2021. Based on the results of the research, it shows that the role of PBB In economic growth in West Pasaman Regency is still very small. Where this can be seen from the PBB contribution to PAD from 2016 to 2021 an average of 2,4%, which means there is very little contribution. This is due to the low public awareness in paying PBB in West Pasaman Regency. So that the realization of PBB is not always achieved. PBB is very influential in increasing PAD, but in fact the PBB is very low. Where it can be seen that the role of PBB on Economic Growth in West Pasaman Regency can be seen by the receipt of PAD. PAD funds will be allocated for smooth development.